Attempt of Real-Time Near-Infrared Fluorescence Imaging Using Indocyanine Green (ICG) in Radical Resection of Gallbladder Cancer: A Case Report - Yu, Yang; Xiang, Lin; Bai, Yuping; Maswikiti, Ewetse Paul; Gu, Baohong; Li, Xuemei; Li, Haiyuan; Zheng, Peng; Zhang, Ying; Chen, Hao (Frontiers in Surgery, 2021)
Surgery is the mainstay of treatment for resectable gallbladder cancer. Near-infrared fluorescence (NIRF) imaging using ICG is an innovation in laparoscopic surgery, which can provide real-time navigation during the whole operation. In this article, we present a 56-year older woman with gallbladder cancer, in which we evaluated the applicability of NIRF imaging using ICG for tumor and biliary tree visualization during the operative procedure of gallbladder cancer. The tumor and biliary tree were clearly visualized by utilizing a green fluorescence dye. The patient was successfully operated radical resection of gallbladder cancer under fluorescence laparoscope, without any complications. According to this case, the utilization of ICG based NIRF imaging is feasible and beneficial in identifying tumors and the biliary tree during radical resection. It can assist in the achievement of a negative margin and lymphatic clearance around the biliary tree. However, further studies are needed to corroborate the results of this case.